Phylogenetic relationships of southern Wallacean ranid frogs (Anura: Ranidae: Hylarana) - Reilly, Sean B.; Arifin, Umilaela; Stubbs, Alexander L.; Karin, Benjamin R.; Kaiser, Hinrich; Frederick, Jeffrey H.; Arida, Evy; Iskandar, Djoko T.; Mcguire, Jimmy A. (Zootaxa, 2022)
Frogs in the family Ranidae are diverse in Asia and are thought to have dispersed to the Sahul Shelf approximately 10 million years ago, where they radiated into more than a dozen species. Ranid species in the intervening oceanic islands of Wallacea, such as Hylarana florensis and H. elberti from the Lesser Sundas and H. moluccana from eastern Wallacea, are assumed to belong to the subgenus Papurana, yet this has not been confirmed with molecular data. We analyzed mitochondrial DNA of Hylarana species from five islands spanning the reported ranges of H. florensis and H. elberti and compared them to confirmed Papurana species and closely related subgenera within Hylarana. We find that the Lesser Sunda H. florensis and H. elberti form a clade that is sister to the rest of the Australo-Papuan Papurana assemblage. Species delimitation analyses and divergence time estimates suggest that populations of H. florensis on Lombok may be distinct from those on Flores at the species level. Likewise, populations of H. elberti on Sumba and Timor may be distinct from each other and from those on Wetar, tshe type locality of H. elberti. Samples from Babar Island thought to be members of H. elberti in fact belong to the wide-ranging H. daemeli, which occurs in northern Australia, across New Guinea, and on the neighboring island of Tanimbar. These results suggest that the Lesser Sundas may have served as a stepping-stone for colonization of the Sahul Shelf and that species diversity of Papurana frogs is underestimated in the Lesser Sundas.